Fungsi, Makna, dan Nilai Budaya Adat Makan Lamang pada Pesta Pernikahan di Kenagarian Sungai Talang Kabupaten Lima Puluh Kota - Tia Ivanka; Fajri Usman; Alex Darmawan (Puitika)
This research is based on the implementation of the custom of eating lamang which is often carried out at weddings and cannot be separated from the traditions in the Kenagarian Sungai Talang community, Lima puluh Kota Regency. This research aims to =ind out the function, meaning and cultural values found in the custom of eating lamang at weddings in Kenagarian Sungai Talang. Research methods and techniques are divided into three stages, namely: data provision stage, data analysis stage, and data analysis results presentation stage. At the data provision stage, the listening method and the pro=icient method were used. The basic technique used in the listen method is the tapping technique and the advanced techniques are the skillful listening and note taking technique. At the data analysis stage, the referential equivalent method and the translational equivalent method were used. The basic technique used is the technique of selecting the determining elements and the advanced technique used is the contrasting comparison technique. Furthermore, in presenting the results of data analysis, the method used is an informal presentation method. The results of this research show that the traditional lamang eating procession contains functions, meanings and cultural values of the language in it